La pratique contraceptive dans la Wilaya de Marrakech (Maroc): niveau, but, évolution et relation avec la fécondité - Samia R’Kha; Abdellatif Baali; Gilles Boëtsch; Émile Crognier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The pattern of family planning was analysed in two communities of the Wilaya of Marrakesh (Morocco). One of them is urban, represented by the city of Marrakesh, and the other is rural and represented by some municipalities of Amizmiz (circle of Amizmiz, province of Haouz, Wilaya of Marrakesh). In general, the use of contraception is quite high, but it is especially high in the urban environment. The analysis of contraception biographies, particularly of the period when contraception use begins and the degree of its regularity, demonstrates the women’s intentions concerning contraception use. The contraception adopted in the urban environment is applied almost exclusively to spacing between births in which regularity is important, whereas in the rural environment two attitudes coexist: the desire for spacing and that for limitation of births. The diffusion of contraception methods began in 1965 for the city and in 1975 for the rural area. The rhythm of transition to contraception was very gradual in the urban environment and much more accelerated in the rural areas. Other differences between the two areas concerning the development of contraception use during the procreative life of the women are discussed. The efficiency of contraception in relation to levels of fertility is proven.